2020
DOI: 10.1021/acs.energyfuels.0c03075
|View full text |Cite
|
Sign up to set email alerts
|

An Unreacted Shrinking Core Model Serves for Predicting Combustion Rates of Organic Additives in Clay Bricks

Abstract: The present study investigates the suitability and restrictions of the unreacted shrinking core model to describe the combustion of a fixed organic substance in a clay matrix, as found in the firing process of clay bricks. The model was applied to the experimental data of isothermal measurements and validated by the model prediction of nonisothermal experiments, which were examined by combustion of mixed clay containing several organic additives in a fluidized bed combustor. Besides reactivity measurements, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Temperature dependency of effective diffusion coefficients is frequently assumed to be exponential and described by an Arrhenius equation (e.g. [ 5 , 28 ]). The present results in Figure 10 show that, in porous media, the actual diffusion mechanism can differ from a progressive rise in temperature by the dominant influence of the Knudsen diffusion regime.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature dependency of effective diffusion coefficients is frequently assumed to be exponential and described by an Arrhenius equation (e.g. [ 5 , 28 ]). The present results in Figure 10 show that, in porous media, the actual diffusion mechanism can differ from a progressive rise in temperature by the dominant influence of the Knudsen diffusion regime.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature dependency of effective diffusion coefficients is frequently assumed to be exponential and described by an Arrhenius equation (e.g. [5,28]). The present results in Figure 10 show that, in porous media, the actual diffusion mechanism can differ from a progressive rise in temperature by the dominant influ- Peng et al found a diffusion coefficient of 0.014 cm 2 /s for a clay brick [4], which is very close to the model prediction represented by Figure 10b, revealing an apparent gas-phase diffusion coefficient at an ambient temperature for sample A of 0.011 cm 2 /s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the variation in the red color intensity directly maps the concentration of M in this system, the concentration of the red dye (C EtBr ) is used to model the entire drug delivery and the reaction for a cancer cell. The concentrations of M at r , s r , cy r , nm and r n are considered as C , s C , cy C , nm C , n respectively [31]. Thus, (i) mass transfer of M through bulk liquid phase, (ii) diffusion of M through cell membrane, (iii) mass transfer of M through cell cytoplasm, (iv) diffusion of M through nuclear membrane, and (v) rate of reaction of cell nucleus (Q) with M can be modeled as…”
Section: Modeling Of Drug Transportmentioning
confidence: 99%
“…At steady state, the reaction-diffusion kinetics on the consumption of M from equations (6)-(10) is given by[31],…”
mentioning
confidence: 99%